2005
DOI: 10.1111/j.1469-7610.2004.00397.x
|View full text |Cite
|
Sign up to set email alerts
|

Practitioner Review: Cognitive rehabilitation for children with acquired brain injury

Abstract: There is an absence of randomised controlled trials and a very limited number of studies using other methodological approaches, providing at this time no conclusive evidence for the efficacy of cognitive rehabilitation for children with acquired brain injury, but a clear need to address a range of methodological difficulties in this field of enquiry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
61
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(63 citation statements)
references
References 50 publications
1
61
0
1
Order By: Relevance
“…For example, the significant outcomes of the Mitii TM group compared to the control group on upper limb functioning, visual perception, and manual dexterity were specific to the modules trained in Mitii TM [25] . Overall this is also consistent with findings from other studies, in which skills practiced improve with online or web-based training, however generalisation to other skills or everyday functioning is not always evident [15,16,21,33] .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…For example, the significant outcomes of the Mitii TM group compared to the control group on upper limb functioning, visual perception, and manual dexterity were specific to the modules trained in Mitii TM [25] . Overall this is also consistent with findings from other studies, in which skills practiced improve with online or web-based training, however generalisation to other skills or everyday functioning is not always evident [15,16,21,33] .…”
Section: Discussionsupporting
confidence: 91%
“…There is a larger body of evidence for children related to EF with an acquired brain injury (ABI) [15][16][17][18][19] , however, the study designs are single cases or small sample sizes [15] . Interventions showing promise in other populations include aerobic exercise, and computerised training for attention and working memory (both aspects of EF) [20,21] .…”
mentioning
confidence: 99%
“…instruction strategies, although these techniques have not been clearly shown to improve attention [Limond and Leeke, 2005]. Integrated and multidisciplinary assessment and coordination of care as part of rehabilitation improves parent understanding, which thus improve overall quality of life and functional outcomes, including self-care skills, fine and gross motor performance and language ability in children after TBI [Tomlin et al, 2002].…”
Section: Postinjury Predictors Traumatic Brain Injurymentioning
confidence: 98%
“…Limond and Leeke [2005] reviewed all published interventions targeting the cognitive domains of attention, memory, and/or executive functioning in children with ABI published and indexed in medical and psychological databases through 2002. On the basis of their analysis of the published studies, there was no conclusive evidence for the efficacy of cognitive reha-bilitation in children with ABI.…”
mentioning
confidence: 99%
“…In contrast, relatively few studies have examined efficacy of intervention techniques for children with brain injury; however, each year this literature is growing. In the past 4 years, there have been two systematic reviews of cognitive interventions for pediatric brain injury [Limond and Leeke, 2005;Laatsch et al, 2007]. In these systematic reviews, studies were identified through a rigorous search of existing databases and each individual study was classified based on the strength of the study design.…”
mentioning
confidence: 99%